Military and Government Technology | From Fail to Win! - Ian Graham (Oxford, United Kingdom Capstone Global Library Ltd, 2010)
Have you ever wondered what went wrong when inventions, structures and technology failed spectacularly? This series provides exciting, cross-curricular, high interest reads into ideas and projects from around the world that did not work as planned.
Keywords: Warfare & Weapons - Weaponry -- Warfare & Weapons - Weaponry